(untitled) (Journal of the College of Basic Education, 2023)
1. Herbert Samuel is British politician from an orthodox Jewish family well established in money and commerce . 2. He was the first Zionist Jewish minister to assume important posts in the successive British governments . He directed the British policy to support the Zionist project in palestine by virtue of his inflecene on British decision making. 3. In 1919, he embraced the Zionist idea of the return to the promised land and the re –establishment of the temple to Erect Grand Israel . This idea serves the British interest to redivect the Jewish migration from western Europe to Palestine with serues , In turn , the Zionist project to establish a core for a Zionist state in palustin . 4.He submitted many memoranda to the British governmed between 1919 and 1915 and he was the first who suggested the capabilities of establishing establishment of Jewish state there . 5- He had an important role in issuing Belfor’s promise in 1917 through his relations with top British officials . This British promise gave the Jews land in Palestine to establish their state . 6. He had high influence on the peace conferece in Paris in 1919 which he attended with the Zionist delegate which submitted a memorand. from the Zionist organization demanding the conference recognition of the historical right of the Jewish people in Palestine . 7. During his appointment as a high commissioner in Palestine from 1920 to 1925 he worked to make Palestine Jewish by opening Palestine to Jewish migration . The number of migrants increased to 84000 and the number of colonies from 44 to 100 . 8. He ruled Palestine by western laws , ignoring the Ottoman laws which deprived the Palestinian people of self – rule . 9. He was able to match the Zionists interests with the British interests . 10. He managed in linking the Zionists interests with the British policies ; yet the problem of finding a homeland for the jews was complicated and he failed to embrace the Jewish migrants .